Strategies for implementing a life project for institutionalized elderly people (Revista Lusófona de Educação, 2025)
This article is the result of a study conducted with 11 technical directors and/or social workers who work in Residential Facilities for the Elderly (ERPI) across various regions of Portugal, ranging from the north to the south of the country. The primary objective of this research was to understand how the life projects of the elderly are planned and outlined at the time of their institutional integration, with the aim of creating a guiding framework for the viable implementation of life projects for institutionalized elderly people.The research highlights the importance of advocating an elderly-centered intervention, actively involving them in the deciding-making process regarding their own life projects, and fostering a safe environment where they feel a sense of belonging and where their autonomy is valued.This study makes a significant contribution by presenting a proposal with guidelines for implementing life projects in ERPIs, which is not always feasible today, promoting active, successful, and person-centered aging.